Effect of particle size variation of stabilized wheat germ on dough processing characteristics and steamed bread quality - Gongqi Zhao; Miaomiao Pan; Xianling Zhang; Gengqing Liao; Yizhou Wu; Yanxia Yang; Liping Yang (Food Chemistry: X)
Wheat germ is a by-product of wheat flour milling and processing, and is valued for being the nutrient-rich center of wheat grains. In this study, hot air-stabilized wheat germ with five different particle sizes (coarse, medium, fine, ultrafine, and very fine) was prepared and mixed with wheat flour (WF) in a ratio of 8:92. The study focused on the effect of particle size of stabilized wheat germ on the thermomechanical, dynamic rheological, and fermentation properties of wheat flour and the quality of steamed bread. The results revealed that the particle size of wheat germ affects the secondary structure of gluten proteins, as the contents of β-sheet and α-helix structures in dough containing very fine wheat germ particles increased to 29.16 % and 25.07 %, respectively. The addition of wheat germ significantly lower starch digestibility of steamed bread. In conclusion, the quality of steamed bread can be improved by controlling the particle size of wheat germ; the incorporation of very fine wheat germ enhanced the quality of steamed bread, while ultrafine grinding weakened the quality. This study serves as a reference for the development of wheat germ-steamed bread and contributes to the promotion of deep processing of wheat germ.